Respuesta :
Answer:
x=3
Step-by-step explanation:
-3x-5y=6
-5 times -3 = 15
-3x+15=6
+3x on both sides
15=6+3x
-6 on both sides
9=3x
divide by 3 on both sides
x=3
If we have the substitution for y, replace the y in the equation with -3
-3x-5(-3)=6
Multiply the -5 with the -3, and when you multiply a negative number with a negative it turns into a positive
-3x+15=6
Bring the 15 over to the other side of the equation to get the x number by itself like this —-> -3x=6-15 and when you cross over a number to the other side of the equation it’s positive or negative sign changes into the opposite
Now subtract
-3x=-9
Divide
-3x = -9
—— ——
-3 -3
And a negative number divided by a negative also makes the number a positive
X=3
-3x-5(-3)=6
Multiply the -5 with the -3, and when you multiply a negative number with a negative it turns into a positive
-3x+15=6
Bring the 15 over to the other side of the equation to get the x number by itself like this —-> -3x=6-15 and when you cross over a number to the other side of the equation it’s positive or negative sign changes into the opposite
Now subtract
-3x=-9
Divide
-3x = -9
—— ——
-3 -3
And a negative number divided by a negative also makes the number a positive
X=3